2022
DOI: 10.3390/ijms23031342
|View full text |Cite
|
Sign up to set email alerts
|

DNA Polymerase-Parental DNA Interaction Is Essential for Helicase-Polymerase Coupling during Bacteriophage T7 DNA Replication

Abstract: DNA helicase and polymerase work cooperatively at the replication fork to perform leading-strand DNA synthesis. It was believed that the helicase migrates to the forefront of the replication fork where it unwinds the duplex to provide templates for DNA polymerases. However, the molecular basis of the helicase-polymerase coupling is not fully understood. The recently elucidated T7 replisome structure suggests that the helicase and polymerase sandwich parental DNA and each enzyme pulls a daughter strand in oppos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 53 publications
(131 reference statements)
0
1
0
Order By: Relevance
“…The genomic annotation of phage BUCT700 showed that 7 ORFs were associated with replication and transcription, including DNA primase/helicase (ORF 20), DNA helicase (ORF 21), DNA polymerase I (ORF 22), 5′–3′ exonuclease (ORF 24), DNA exonuclease (ORF 25), exonuclease (ORF 26), and DNA-dependent RNA polymerase (ORF 34). During DNA replication, a DNA helicase and a DNA polymerase cooperatively unwind the parental DNA ( 29 ). Although DNA polymerase I (ORF 22) has exonuclease activity, phage BUCT700 still carries 3 genes (ORF 24, 25, and 26) encoding exonucleases.…”
Section: Resultsmentioning
confidence: 99%
“…The genomic annotation of phage BUCT700 showed that 7 ORFs were associated with replication and transcription, including DNA primase/helicase (ORF 20), DNA helicase (ORF 21), DNA polymerase I (ORF 22), 5′–3′ exonuclease (ORF 24), DNA exonuclease (ORF 25), exonuclease (ORF 26), and DNA-dependent RNA polymerase (ORF 34). During DNA replication, a DNA helicase and a DNA polymerase cooperatively unwind the parental DNA ( 29 ). Although DNA polymerase I (ORF 22) has exonuclease activity, phage BUCT700 still carries 3 genes (ORF 24, 25, and 26) encoding exonucleases.…”
Section: Resultsmentioning
confidence: 99%